Analysis of Notary's Obligation to Provide Notarial Pro Bono Services to Financially Disadvantaged Individuals (A Studi on The Notaries in Medan) - Liza Afriani Harahap (CERED Indonesia Institute, 2023)
As public officials appointed by the state, notaries do not receive state honoraria; however, they receive honoraria for legal services rendered in accordance with their authority. The use of notary services is affected by the ability to pay (ATP) due to the financial ability. However, according to Article 37 paragraph (1) of the Law on Notary Position and Article 3 number (7) concerning the Notary Code of Ethics for the Extraordinary Congress of the Indonesian Notary Association held in Banten in 2005, “Notaries are obliged to provide notarial pro bono services to financially disadvantaged individuals”. The implementation of these notarial pro bono services for financially disadvantaged individuals in Medan has been going well due to the humanity, notary's morality, and integrity.